2022
DOI: 10.1177/21582440221079936
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Asymmetric Effect of Oil Price on the Economic Growth in Malaysia: Applying Augmented ARDL and Nonlinear ARDL Techniques

Abstract: This paper attempts to investigate if the effect of oil price on growth is asymmetrical for Malaysia, a small-open-dynamic oil-exporting country, over a period from 1981 to 2017. The empirical method employed in this study is the augmented autoregressive distributed lag model (ARDL) bound test approach and the recent innovative nonlinear autoregressive distributed lag (NARDL) model. Results suggest that neglecting nonlinearities can lead to misleading results. More precisely, the result reveals that adjustment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…In contrast, Prabheesh and Laila, (2020) have produced positive shocks in crude and palm oil prices to enhance economic growth in Indonesia, whereas a negative shock in these oil prices retards economic growth. Several others have concluded that a negative shock in oil price hampers economic growth in oil-exporting countries and a positive shock in oil price enhances economic growth in these countries (Berument et al, 2010;Kriskkumar et al, 2022;Kriskkumar and Naseem, 2019), hence, these studies are contrary to the findings of our study that a negative shock in oil price enhances the economic growth in Somalia.…”
Section: Discussion Of the Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast, Prabheesh and Laila, (2020) have produced positive shocks in crude and palm oil prices to enhance economic growth in Indonesia, whereas a negative shock in these oil prices retards economic growth. Several others have concluded that a negative shock in oil price hampers economic growth in oil-exporting countries and a positive shock in oil price enhances economic growth in these countries (Berument et al, 2010;Kriskkumar et al, 2022;Kriskkumar and Naseem, 2019), hence, these studies are contrary to the findings of our study that a negative shock in oil price enhances the economic growth in Somalia.…”
Section: Discussion Of the Resultscontrasting
confidence: 99%
“…If the country is a net oil importer such as Somalia, a positive shock in oil price will harm economic growth. If the country is a net oil exporter, a positive shock in oil price will have a positive impact on economic growth (Kriskkumar et al, 2022). Regarding the longrun results of the study, it is observed that a positive shock in oil price is inconsequential in the long run; whereas a negative shock in oil price has a constructive role in enhancing economic growth in the long run.…”
Section: Discussion Of the Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Therefore, formulating PGEB poses a certain degree of risk to its reliance on aggregate revenue collection. Within the oil revenue sector, both direct and indirect effects could be channelled via government budget expenditure (Kriskkumar, Naseem & Azman-Saini, 2022;Shangle & Solaymani, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%